The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1980-5373-mr-2018-0270
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Process Parameters of Equal Angular Channel Pressing According to the Measurement Results of Microstructural Homogeneity

Abstract: The aim of the present work is to discuss process parameters effect on microstructure evolution and formation mechanism of ultrafine grains. As plastic deformation technique Equal Channel Angular Pressing (ECAP) method used pure Ti G4 rods processed in order to obtain fine grained micro structure. Equal Chanel Angular Pressing technique was conducted at different processing route, process temperature, pressing velocity with an orthogonal design to critically evaluate the significance of these process parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
4
0
2
Order By: Relevance
“…[27] In another study, experimental design was used to determine the optimal ECAP parameters for pure titanium of grade 4, and it was concluded that 573 K is the optimal processing temperature for a reasonably homogeneous microstructure. [28] Nevertheless, some other experiments demonstrated the feasibility of conducting the ECAP processing of CP Ti of grade 1 at room temperature using a low pressing speed, a higher channel angle of 120 or 135 , and/or a special composite lubricant. [29][30][31][32] These experiments gave values for the YS of %680 MPa after 1 pass [29] and after eight passes it was %710 MPa with a UTS of %790 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] In another study, experimental design was used to determine the optimal ECAP parameters for pure titanium of grade 4, and it was concluded that 573 K is the optimal processing temperature for a reasonably homogeneous microstructure. [28] Nevertheless, some other experiments demonstrated the feasibility of conducting the ECAP processing of CP Ti of grade 1 at room temperature using a low pressing speed, a higher channel angle of 120 or 135 , and/or a special composite lubricant. [29][30][31][32] These experiments gave values for the YS of %680 MPa after 1 pass [29] and after eight passes it was %710 MPa with a UTS of %790 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…From early experiments on the processing of pure titanium by ECAP, it was concluded that the processing required a high pressing temperature of at least ≈550 K because, due to the limited number of active slip systems in titanium, processing at lower temperatures leads to a segmentation of the ECAP billets wherein the samples either break or they become divided into discrete segments that are held together by small portions of material lying along the bottom surfaces of the billets . In another study, experimental design was used to determine the optimal ECAP parameters for pure titanium of grade 4, and it was concluded that 573 K is the optimal processing temperature for a reasonably homogeneous microstructure …”
Section: Discussionmentioning
confidence: 99%
“…Specimens were prepared with an electro-discharge machine in a dog bone shape with 6 Â 1.5 Â 22 mm (wide, thickness, and length) similar to the previous papers. [25,26] Three repetitive tests were performed at a room temperature at 0.01 s À1 with a Zwick Roell with a capacity of 25 tones tensile testing machine. Tensile test specimens were taken from the midsection of each specimen and parallel to incremental pressing direction.…”
Section: Methodsmentioning
confidence: 99%
“…Saf Zn ile gerçekleştirilen deneylerde ise Şekil 4'de gözlemleneceği üzere özellikle 10. pasodan sonra numunenin kenar kısmında sertlik değeri merkeze göre daha düşüktür. Daha önce düşük istiflenme enerjisine sahip malzemeler ile gerçekleştirilen plastik deformasyon işlemlerinden sonra kesitteki gerinim miktarının artması ve pekleşme sebebi ile sertliğin yükseldiği gözlemlenmiştir [12], [19]. Hızlı yeniden kristalleşme özelliğine sahip malzemelerin aşırı plastik deformasyon sonrasında sertlik değerlerinde düşüşler gözlemlenmiştir [15], [20].…”
Section: şEkil 1 çEkme Numunesi Ve Numune Tutucuunclassified
“…APD teknikleri tane yapısını inceltirken malzeme özelliklerini iyileştirmektedir. APD teknikleri ile malzemenin sertlik değerlerinin ve mekanik dayanımının iyileştirildiği gözlemlenmiştir [12]. Özelliklerin bu yönde iyileşmesi daha ince ve hafif tasarımların kullanımını mümkün kılmaktadır.…”
Section: Introductionunclassified